Agradecimiento a los árbitros (Sosquua, 2020)
Agradecemos la participación de los siguientes árbitros: Laura María Rodríguez Gutiérrez, Universidad de Antioquia, Colombia Luis Alfonso Vidal Ramírez, Colegio Mayor de Antioquia, Colombia Karen Paola Ochoa Espitia, Independientes, Colombia Olga Judith García Molano, Universidad Pedagógica de Colombia, ColombiaFrank Ángel Lemoine Quintero, Universidad Laica Eloy Alfaro de Manabí, EcuadorCarolina Garzón Medina, Universidad Santo Tomás, ColombiaFabián Herrera Morales, Universidad de Caldas, ColombiaRicardo Varela Villalba, Universidad Autónoma de Bucaramanga, ColombiaArney Alfonso Vega Martínez, Universidad del Sinú, ColombiaCarlos Andrés Carreño Hernández, Universidad Pedagógica de Colombia, Colombia Joaquín Humberto Fontecha Fontecha, Universidad de Santander, Colombia